Suspension of fertility treatment during the COVID-19 pandemic: views, emotional reactions and psychological distress among women undergoing fertility treatment - Marom Haham, Lilach (Reprod Biomed Online, 2021)
RESEARCH QUESTION: What are the views and emotional reactions of patients towards the suspension of fertility treatment during the COVID-19 pandemic, and what are the factors affecting their psychological distress? DESIGN: A cross-sectional study conducted in an academic fertility centre. Online questionnaires were distributed between 18 April 2020 and 23 April 2020 to patients whose treatment cycle had been postponed or discontinued. The outcome measures included agreement with the reproductive society guidelines to postpone treatments; willingness to resume treatments, given the choice; patients’ emotional reactions; and psychological distress level, measured by the Mental Health Inventory validated scale. A multivariate linear regression was conducted to identify factors associated with psychological distress. RESULTS: Because of the small number of male respondents, only women were included in the analysis (n = 181). Forty-three per cent expressed disagreement with the guidelines and 82% were willing to resume treatments, given the choice. Sadness and anxiety were the most common emotional reactions expressed towards the guidelines. In the multivariate analysis, COVID-19-related anxiety (B = 0.145, P = 0.04) and disagreement with treatment suspension (B = –0.44, P = 0.001) were found to be significantly associated with patients' psychological distress. Background characteristics of patients did not contribute significantly to their distress. CONCLUSIONS: Suspension of fertility treatment during the initial phase of the COVID-19 pandemic was associated with patients' negative emotional reactions. Anxiety related to COVID-19 and disagreement with treatment suspension were found to be significantly associated with psychological distress among women undergoing fertility treatment, regardless of their background characteristics. Our findings suggest the need to monitor the mental health of patients and provide psychological support should a shutdown of fertility care re-occur.